2017
DOI: 10.1111/peps.12253
|View full text |Cite
|
Sign up to set email alerts
|

Considering self‐interests and symbolism together: How instrumental and value‐expressive motives interact to influence supervisors’ justice behavior

Abstract: Drawing upon functional theories of attitudes and the organizational justice literature, the current research suggests that people's attitudes toward justice likely serve an instrumental function (grounded in self‐interest, rewards maximization, and punishment minimization) as well as a value‐expressive function (grounded in the expression of self‐concept and values). Importantly, these two functions co‐exist and interact to influence supervisors’ justice behavior and the consistency of such behavior via super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 103 publications
(231 reference statements)
1
39
0
1
Order By: Relevance
“…With strong support from the human resources department, invitations to participate were sent to 569 supervisors and, for each supervisor, one randomly selected subordinate. We sent participants links to online surveys via WeChat, a widely used messaging application that has been used for collecting data in recent studies (e.g., Ju et al, 2019; Qin et al, 2018). Each participant was rewarded with RMB 20 (approximately US$ 3) per survey for their time.…”
Section: Methodsmentioning
confidence: 99%
“…With strong support from the human resources department, invitations to participate were sent to 569 supervisors and, for each supervisor, one randomly selected subordinate. We sent participants links to online surveys via WeChat, a widely used messaging application that has been used for collecting data in recent studies (e.g., Ju et al, 2019; Qin et al, 2018). Each participant was rewarded with RMB 20 (approximately US$ 3) per survey for their time.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that, these values are comparable to those ICC values reported in the organizational behavior literature (see Bliese, 2000; Liao & Chuang, 2007; Qin, Hom, & Xu, in press; Schneider, White, & Paul, 1998). Some scholars suggested that relatively low ICC[2] should not prevent aggregation if aggregation can be justified by theory and high r wg and significant between-group variance (Chen & Bliese, 2002; Kozlowski & Hattrup, 1992; Qin, Ren, Zhang, & Johnson, 2018). Thus, we conducted the aggregation, while acknowledging that “the relationships between the aggregated measures with low ICC[2] and the other study variables might be underestimated” (Liao & Chuang, 2007, p. 1012).…”
Section: Study 2: Methodsmentioning
confidence: 99%
“…perceived supervisory support, an individual-level construct; Eisenberger et al, 2002) may act as a similar buffer (though differential support may backfire; Seo et al, 2018). Future research might thus assess perceived supervisory support as well as other resources, such as supervisor justice treatment (Qin et al, 2017b), and families or friends relocating to the same urban community who can help migrants adapt to urban work and life. Some job demands (e.g.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%